How Have We Approached Teaching Our Son To Read English?: An Autoethnography - Hendrayana, Afdal Ade; Pujowati, Epi Stiyo (Jurnal Sasindo UNPAM, 2024)
This autoethnographic study explores the process of teaching English reading to a young child, starting at the age of two, in a non-native English-speaking family. The study aims to understand the nuances and effects of early literacy interventions, highlighting the importance of systematic instruction in phonemic awareness, phonics, fluency, vocabulary, and comprehension strategies. Through detailed personal experiences, the study illustrates the progression of learning stages from alphabet recognition to the development of sight word recognition and orthographic mapping. By integrating education theories with longitudinal personal experiences, this study provides insights into effective teaching practices and child-centered learning approaches that can significantly influence early literacy development. The findings suggest that early, structured reading education is critical in fostering reading proficiency, offering a blueprint for parents and teachers in similar educational settings.